2018
DOI: 10.1038/s41598-018-27896-y
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic change of neutrophil to lymphocyte ratio can predict clinical outcome in stage I-III colon cancer

Abstract: Whether the dynamic change of neutrophil to lymphocyte ratio (delta-NLR) can predict the outcome in various malignancies remained controversial. The delta-NLR has not been evaluated in colon cancer. Thus, we conducted the study to evaluate the predictive value of the delta-NLR in patients with colon cancer who underwent curative resection. Three-hundred and fifty-four patients with stage I-III colon cancer were retrospectively analysed. Clinicopathological features, preoperative NLR and postoperative NLR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…Prior studies have reported a variety of inflammation markers as predictors for oncological outcomes in multiple types of cancer 4 24 . In NSCLC, preoperative NLR, PLR and PNI have been demonstrated to predict cancer recurrence or mortality after tumour resection 4 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported a variety of inflammation markers as predictors for oncological outcomes in multiple types of cancer 4 24 . In NSCLC, preoperative NLR, PLR and PNI have been demonstrated to predict cancer recurrence or mortality after tumour resection 4 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses have adjusted for a detailed list of covariates, and preoperative NLR remained significantly associated with cancer recurrence and all-cause mortality. Absolute change of lymphocyte count and dynamic change of NLR have also been reported to predict outcomes in liver cancer and colon cancer 22,24 . However, we did not confirm the prognostic values of these indexes in NSCLC.…”
Section: Continuous Nlrmentioning
confidence: 98%
“…Our results are in line with the study ( 32 ). Nonetheless, the post-NLR was previously reported to be an important prognostic factor in many cancers, including gastric cancer ( 33 ), hepatocellular carcinoma ( 34 ), renal cell carcinoma ( 35 ) and CRC ( 36 ), but it was noted that it could be affected by many factors. For example, a relatively high post-NLR was associated with surgery-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammatory responses are thought to play a role in tumor progression by inducing angiogenesis and inhibiting apoptosis and DNA damage, tumor proliferation, and metastasis. 3,11,12 In addition to the high-risk factors associated with different tumor characteristics, the host's immune system also plays a role in the invasion or metastasis of colon cancer. 13 The host inflammatory response to cancer cells is also associated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%